Efforts to Improve Customer Satisfaction with Wood Pellets Using the CARTER Method - Marnoto Marnoto; Sopi Sopi; Arini Novandalina (Lembaga Penelitian dan Pengabdian kepada Masyarakat ITATS, 2026)
This study aims to evaluate and improve customer satisfaction with wood pellets in Semarang by applying the CARTER method (Compliance, Assurance, Reliability, Tangibles, Empathy, and Responsiveness). A quantitative approach with an explanatory design was chosen to measure the impact of the CARTER intervention on customer perceptions. The sample consisted of 100 active wood pellet customers who were purposively selected (customers with ≥ 1 year of experience, had submitted complaints, and were willing to participate). Primary data was collected through a validated Likert scale 1–5 questionnaire (Cronbach's α gt; 0.6). The analysis included descriptive statistics, validity and reliability tests (SPSS 25). The results show that all CARTER dimensions scored an average of ≥ 4.0 on a 1–5 scale, indicating generally positive perceptions. Regression analysis revealed that Empathy and Responsiveness had the most significant impact on overall satisfaction. Based on the findings, the researcher recommends optimizing the logistics system through the use of digital platforms to improve delivery timeliness, enhancing service training focused on product expertise and quick solution capabilities, and strengthening transparency in communication regarding technical standards and environmental regulations to maintain customer trust. This study contributes theoretically by filling a research gap in the literature on customer satisfaction with wood pellets, which has primarily focused on technical production aspects. Practically, the findings offer a CARTER framework that can be adopted by wood pellet producers and distributors in Indonesia to enhance regional competitiveness and support the achievement of national renewable energy mix targets.